The incremental predictive information associated with using theoretical new Keynesian DSGE models versus simple linear alternatives - Oleg Korenok; Norman R. Swanson (Rutgers University, Department of Economics, 2005)
In this paper we construct output gap and inflation predictions using a variety of DSGE sticky price models. Predictive density accuracy tests related to the test discussed in Corradi and Swanson (2005a) as well as predictive accuracy tests due to Diebold and Mariano (1995) andWest (1996) are used to compare the alternative models. A number of simple time series prediction models (such as autoregressive and vector autoregressive (VAR) models) are additionally used as strawman models. Given that DSGE model restrictions are routinely nested within VAR models, the addition of our strawman models allows us to indirectly assess the usefulness of imposing theoretical restrictions implied by DSGE models on unrestricted econometric models. With respect to predictive density evaluation, our results suggest that the standard sticky price model discussed in Calvo (1983) is not outperformed by the same model augmented either with information or indexation, when used to predict the output gap. On the other hand, there are clear gains to using the more recent models when predicting inflation. Results based on mean square forecast error analysis are less clear-cut, although the standard sticky price model fares best at our longest forecast horizon of 3 years, and performs relatively poorly at shorter horizons. When the strawman time series models are added to the picture, we find that the DSGE models still fare very well, often winning our forecast competitions, suggesting that theoretical macroeconomic restrictions yield useful additional information for forming macroeconomic forecasts.
Keywords: E12; E3; C32; 330; Model selection; predictive density; sticky information; sticky price